2023
DOI: 10.3390/rs15133227
|View full text |Cite
|
Sign up to set email alerts
|

Improved PPP-RTK by Considering the Non-Homogeneous Uncertainty of the ionosphere with a Spatial Three-Direction Model

Abstract: The ultimate goal of PPP-RTK is to achieve rapid ambiguity resolution, which is influenced by the prior precision of the external ionospheric information. This study proposes a method for determining the precision of ionospheric corrections for each satellite. In this method, an 8 min piece-wise function linearly related to the spatial three-direction distance components (SDC) within the geocentric coordinate system is constructed. By exploiting the SDC model, the user can calculate the precision of the ionosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Moreover, research works have reported the implementation of the PPP-RTK technique within smartphones [ 17 , 18 ]. In light of the central role of ionosphere modelling, particular attention has been paid to this aspect in the research community [ 19 , 20 , 21 , 22 , 23 ]. Wang and Zhang [ 24 ] developed a concept of all-frequency PPP-RTK tested in a vehicle-borne experiment carried out in Wuhan City; their results showed that the percentage of the epochs with a horizontal positioning error of less than 0.1 m was increased by 5–30% from conventional to all-frequency PPP-RTK.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research works have reported the implementation of the PPP-RTK technique within smartphones [ 17 , 18 ]. In light of the central role of ionosphere modelling, particular attention has been paid to this aspect in the research community [ 19 , 20 , 21 , 22 , 23 ]. Wang and Zhang [ 24 ] developed a concept of all-frequency PPP-RTK tested in a vehicle-borne experiment carried out in Wuhan City; their results showed that the percentage of the epochs with a horizontal positioning error of less than 0.1 m was increased by 5–30% from conventional to all-frequency PPP-RTK.…”
Section: Introductionmentioning
confidence: 99%